Pendaftaran Indikasi Geografis Tahu Sumedang Sebagai Aset Potensial Daerah - Yudha agung nugraha; Imam Haryanto (Universitas Jambi, Fakultas Hukum, 2021)
Abstract This artikel examines the Barriers to Registration of Geographical Indications of Sumedang Tofu as a Regional Potential Asset, and the Impact on its Inclusion in Geographical Indications. The purpose of this journal is to know the barriers to registration of tofu and tofu geographic indications and their impact on their inclusion in geographic indications. The research method used in the research is Normative Juridical Research which means that it is carried out by examining library materials or secondary materials, then analyzing the issues concerning Geographical Indications and their benefits to the region from which it is originated. The result of the analysis raises 2 themes discussed here: Barriers to Registration of Geographical Indications of Sumedang Tofu, and the impact on Product Inclusion in Geographical Indications. The study of these two themes is very useful to understand the Importance of Registration of Geographical Indications and also the benefits generated by inclusion in Geographical Indication products. Abstrak Artikel ini mengkaji tentang Hambatan Pendaftaran Indikasi Geografis Tahu Sumedang Sebagai Aset Potensial Daerah, dan Dampak terhadap Pencantumanya Kedalam Indikasi Geografis . Tujuan Jurnal ini adalah untuk Mengetahui Hambatan Pendaftaran Indikasi Geografis Tahu Sumedang Serta Dampak terhadap pencantumannya kedalam indikasi Geografis. Metode Penelitian yang digunakan dalam penelitian yaitu Penelitian Yuridis Normatif yang berarti dilakukan dengan cara meneliti bahan pustaka atau bahan sekunder., kemudian menganalisis tentang persoalan-persoalan yang menyangkut tentang Indikasi Geografis dan manfaatnya Terhadap daerah yang menjadi asalnya. Hasil analisis memunculkan 2 tema yang dibahas di sini: Hambatan Pendaftaran Indikasi Geografis Tahu Sumedang, serta dampak terhadap Pencantuman Produk Kedalam Indikasi Geografis. Kajian tentang kedua tema tersebut sangt berguna untuk memahami Pentingnya Pendaftaran Indikasi Geografis dan juga Manfaat yang dihasilkan oleh pencantuman kedalam produk Indikasi Geografis.